2014
DOI: 10.1016/j.febslet.2014.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability to resist to complement lysis and invade host cells mediated by MBL in R4 and 860 strains of Trypanosoma cruzi

Abstract: a b s t r a c tTo produce an infection Trypanosoma cruzi must evade lysis by the complement system. During early stages of infection, the lectin pathway plays an important role in host defense and can be activated by binding of mannan-binding lectin (MBL) to carbohydrates on the surface of pathogens. We hypothesized that MBL has a dual role during parasite-host cell interaction as lectin complement pathway activator and as binding molecule to invade the host cell. We used two polarized strains of T. cruzi, R4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Flow cytometry analysis of parasite lysis (Fig. A and B) indicated epimastigote lysis kinetics very similar to those already shown for other T. cruzi strains (Cestari et al ., ; Evans‐Osses et al ., ), with 91 and 100% lysed cells after 15 and 30 min of FHS exposure (Fig. B).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Flow cytometry analysis of parasite lysis (Fig. A and B) indicated epimastigote lysis kinetics very similar to those already shown for other T. cruzi strains (Cestari et al ., ; Evans‐Osses et al ., ), with 91 and 100% lysed cells after 15 and 30 min of FHS exposure (Fig. B).…”
Section: Resultsmentioning
confidence: 86%
“…As we used nonimmune serum, and the Ca ++ chelating agent EGTA strongly inhibits epimastigote killing (Fig. B), parasite lysis was most likely mediated primarily by the lectin pathway of complement activation, as already shown (Cestari and Ramirez, , ; Evans‐Osses et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, three non-synonymous [18]. Lectin complement proteins have been associated with many infectious diseases including intra and extracellular infections [22][23][24][25]. Our earlier study has shown that, another analogous lectin complement protein ficolin-2 was associated with occurrence of VL [26].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…In a mouse model of T. cruzi infection, MBL influences host resistance and pathology (Rothfuchs et al 2012). In some strains of T. cruzi, MBL mediates resistance to complement lysis of the parasite and enhances invasion of host cells (Evans-Osses et al 2014).…”
Section: Interaction Of Collectins With Protozoal and Helminth Pathogensmentioning
confidence: 99%